Convergence of inflammatory response: Salivary cytokine dynamics in coronavirus disease 2019 and periodontal disease - Shipra Gupta; Ritin Mohindra; Manisha Ramola; Poonam Kanta; Mohita Singla; Meenakshi Malhotra; Nishant Mehta; Ashima Goyal; Mini P. Singh (Wolters Kluwer Medknow Publications, 2024)
Background: Periodontal disease is associated with immune dysregulation, and cytokines released can add on to the coronavirus disease 2019 (COVID-19)-associated cytokine storm, further worsening the related adverse outcomes. Specific studies investigating cytokine levels in COVID-19 patients with periodontal disease are lacking. Examining the correlation between these conditions could aid in categorizing risk categories, determining referrals, and strengthening oral hygiene protocols. The current study sought to evaluate cytokine levels in the saliva of COVID-19-positive patients with and without periodontal disease. Materials and Methods: Twenty-six COVID-19-positive patients were subjected to periodontal examination, saliva collection, and assessment of cytokine levels through cytokine bead-based multiplex assay, using fluorescence-encoded beads with flow cytometry (BD FACS LSRFortessa). Eleven cytokines were assessed (interleukin [IL] 2, 4, 6, 10, 17A, and interferon-gamma (IFN-gamma), tumor necrosis factor-alpha (TNF-α), chemokine ligand 2 (CCL2/monocyte chemoattractant protein-1), C-X-C motif chemokine ligand (CXCL) 8/IL 8, CXCL 9/monokine-induced gamma interferon [MIG]), and CXCL 10 (chemokine IFN-gamma inducible protein 10 kDa). The cytokine levels of the recruited subjects were also compared graphically with the salivary cytokine levels reported in the literature for health, COVID-19, and periodontal disease alone. Results: Out of 26 COVID-19-positive patients, 17 had periodontal disease. Levels of all cytokines were raised in patients with both diseases when compared to values reported in literature for health, periodontal disease alone, or COVID-19 alone. However, there was no statistical difference among the recruited subjects for IL-2, IL-4, IL-6, IL-10, IL-17A, IFN-gamma, TNF-α, CCL2, CXCL 8, and CXCL 10. MIG levels were found to be higher in periodontally healthy, COVID-19-positive subjects (P = 0.01). Conclusions: Periodontal disease might contribute to the COVID-19-induced cytokine storm, potentially amplifying its impact.